Environmental effects of the Deepwater Horizon oil spill: A review. Issue 1 (15th September 2016) - Beyer, Jonny; Trannum, Hilde C.; Bakke, Torgeir; Hodson, Peter V.; Collier, Tracy K.
Abstract: The Deepwater Horizon oil spill constituted an ecosystem-level injury in the northern Gulf of Mexico. Much oil spread at 1100–1300 m depth, contaminating and affecting deepwater habitats. Factors such as oil-biodegradation, ocean currents and response measures (dispersants, burning) reduced coastal oiling. Still, > 2100 km of shoreline and many coastal habitats were affected. Research demonstrates that oiling caused a wide range of biological effects, although worst-case impact scenarios did not materialize. Biomarkers in individual organisms were more informative about oiling stress than population and community indices. Salt marshes and seabird populations were hard hit, but were also quite resilient to oiling effects. Monitoring demonstrated little contamination of seafood. Certain impacts are still understudied, such as effects on seagrass communities. Concerns of long-term impacts remain for large fish species, deep-sea corals, sea turtles and cetaceans. These species and their habitats should continue to receive attention (monitoring and research) for years to come. Graphical abstract: Highlights: The environmental fate of spilled oil and gas The biological/ecotoxicological effects in offshore ecosystems The effects in nearshore and coastal sites The effects on long-lived marine organisms